Secure quantum key distribution system by applying decoy states protocol - Sura Adil Abbas; Nael A. Al-Shareefi (Universitas Ahmad Dahlan, 2022)
Secure quantum key distribution (QKD) promises a revolutionizing in optical applications such as encryption, and imaging. However, their implementation in real-world scenarios continues to be challenged. The goal of this work is to verify the presence of photon number splitting (PNS) attack in quantum cryptography system based on BB84 protocol and to obtain a maximum secure key length as possible. This was realized through randomly interleaving decoy states with mean photon numbers of 5.38, 1.588, and 0.48 between the signal states with mean photon numbers of 2.69, 0.794, and 0.24. Experiment results show that a maximum secure key length obtained from our system, which ignores eavesdropping cases, is 125 with 20% decoy states and 82 with 50% decoy states for mean photon number of 0.794 for signal states and 1.588 for decoy states.